The Role of Daily High Dose Vitamin D In the Prevention of Post-Operative Vitamin D Deficiency In Children with Congenital Heart Disease - McNally, James Dayre (Université d'Ottawa / University of Ottawa, 2015)
Background: With usual supplementation practices, most children are Vitamin D Deficient (VDD) following Congenital Heart Disease (CHD) surgery and alternative regimens need consideration. Methods/Results: i) A systematic review identified 88 pediatric trials of high dose vitamin D. Studies evaluating the Institute of Medicine (IOM) Tolerable Upper Intake Level (UL) did not rapidly normalize levels, while loading therapy (≥ 40000 IU) did so within 3 days. Hypercalcemia occurred more often with doses above 400000 IU. ii) A double blind RCT was designed to determine whether pre-operative administration of the IOM UL can prevent post-operative VDD. Results after the first 30 participants completed study procedures demonstrated it was possible to recruit (1.8 patients per month) and complete study procedures (i.e. blood collection). Unfortunately few participants (45%) received more than 30 doses of study drug. Conclusion: Prevention of post-operative VDD in the majority of CHD patients will require alternatives to the IOM recommendations.
Keywords: Congenital Heart Disease; Vitamin D; Systematic Review; Randomized Controlled Trial